Apical Transportation, Centering Ability, and Cleaning Effectiveness of Reciprocating Single-file System Associated with Different Glide Path Techniques - Carvalho, Guilherme Moreira de; Sponchiado Junior, Emilio Carlos; Bittencourt Garrido, Angela Delfina; Comelli Lia, Raphael Carlos [UNESP]; Roberti Garcia, Lucas da Fonseca [UNESP]; Franco Marques, Andre Augusto (Elsevier B.V., 2015)
Introduction: The aim of this study was to evaluate the apical transportation, the centering ability, and the cleaning effectiveness of a reciprocating single-file system associated to different glide path techniques. Methods: The mesial root canals of 52 mandibular molars were randomly distributed into 4 groups (n = 13) according to the different glide path techniques used before biomechanical preparation with Reciproc System (RS): KF/RS (sizes 10 and 15 K-files), NGP/RS (no glide path, only reciprocating system), PF/RS (sizes 13, 16, and 19 Path File instruments), and NP (no preparation). Cone-beam computed tomography analysis was performed before and after instrumentation for apical third images acquisition. Apical transportation and its direction were evaluated by using the formula D = (X1 - X2) - (Y1 - Y2), and the centering ability was analyzed by the formula CC = (X1 - X2/Y1 - Y2 or Y1 - Y2/X1 - X2). The samples were submitted to histologic processing and analyzed under a digital microscope for debris quantification. The values were statistically analyzed (Kruskal-Wallis, the Dunn multiple comparisons test, P < .05). Results: All groups had similar apical transportation values, with no significant difference among them (P > .05). Groups had a tendency toward transportation in the mesial direction. No technique had perfect centering ability (=1.0), with no significant difference among them. KF/RS had larger amount of debris, with statistically significant difference in comparison with NGP/RS (P > .05). Conclusions: The different glide path techniques promoted minimal apical transportation, and the reciprocating single-file system tested remained relatively centralized within the root canal. Also, the different techniques interfered in the cleaning effectiveness of the reciprocating system.
Keywords: Apical transportation; centering ability; cleaning effectiveness; glide path; reciprocating motion